ANALISIS PENGARUH FAKTOR BAURAN PEMASARAN JASA TERHADAP KEPUASAN NASABAH (Studi Kasus BNI Syariah Kantor Cabang Cinere) - Bisri Bisri; Herlin widasiwi setianingrum (Universitas Bina Sarana Informatika, 2018)
This study aims to analyze the influence of marketing mix (Product, Price / Interest, Promotion, Place, Person / Officer bank, Physical Facility, and Service process) simultaneously and partially to customer satisfaction. Sampling method is using convenience sampling method. The data analyzing by multiple regression method. The results is the marketing mix influence simultaneously to customer satisfaction. Marketing mix partially effect on Customer satisfaction is only influenced by promotion variable and service process variable with t value 2,514> t table 1,984 and service process variable obtained t arithmetic 2,331> t table 1,984. Keywords: Marketing mix, costumer satisfaction and multiple regression Keywords: Marketing mix, multiple regression and customer satisfaction.